Comprehensive Facies Analysis and Depositional Environments of the Kikim Formation, Garba Mountain, South Palembang Subbasin, Indonesia - Daryono, Sapto Kis; Idarwati, Idarwati (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2024)
This study provides an exhaustive facies analysis of the Kikim Formation within the Garba Mountain area of the South Palembang Subbasin, emphasizing the stratigraphic significance and depositional environments during the Paleogene period. Utilizing field data collected from the Bumi Agung and Batu Belang measurement lines, this research categorizes various lithofacies using Miall’s (1978) classification scheme, identifying eight distinct lithofacies and four facies associations indicative of a predominantly fluvial depositional setting. The results depict a detailed sedimentological framework, showing that the Kikim Formation was characterized by a braided river system with significant gravel and sandstone deposits. This analysis not only sheds light on the geological history and processes shaping the South Sumatra Basin but also enhances the understanding of its potential hydrocarbon reservoirs. By detailing the lithological diversity and facies distribution, this paper contributes to the broader geological knowledge required for effective exploration and management of the region's natural resources.